Evaluation of the Isotopic Abundance Ratio of Consciousness Energy Healing Treated L-Tryptophan Using LC-MS Spectrometry - Dahryn, Trivedi; Mahendra, Kumar Trivedi; Alice, Branton; Snehasis, Jana (Journal of Biotechnology and Biomedical Science, 2021)
L-tryptophan is an essential α-amino acid, necessary for the normal growth in newborns, nitrogen balance in adults, protein synthesis, precursor of serotonin, melatonin, niacin, and albeit inefficiently in human, also the precursor of indole alkaloids and auxins in plants. This current study was designed to investigate the impact of the Trivedi Effect®-Biofield Energy Healing Treatment (Blessing) on the structural properties and the isotopic abundance ratio of L-tryptophan using LC-MS analytical technique. L-tryptophan sample was divided into two parts, one part of L-tryptophan was considered as the control sample (no Biofield Energy Treatment was provided), while the second part was treated with the Trivedi Effect®-Consciousness Energy Healing Treatment/Blessing remotely by a renowned Biofield Energy Healer, Dahryn Trivedi and termed as the treated sample. The mass spectra of both the control and treated samples with respect to the chromatographic peak at retention time (Rt) 2.1 minutes exhibited the mass of the molecular ion peak adduct with hydrogen ion at m/z 205.08 (calcd for C11H13N2O2+, 205.1), along with low molecular fragmented mass peaks at m/z 188, 159, and 102 for C11H12N2O2+, C10H11N2+, and C8H6+, respectively were also observed. The isotopic abundance ratio of PM+1/PM (2H/1H or 13C/12C or 15N/14Nor17O/16O) in the treated L-tryptophan was significantly increased by 35.93% compared with the control sample. Hence,the 13C, 2H, 15N, and 17O contributions from C11H13N2O2+ to m/z 206.08 in the treated L-tryptophan was significantly increased compared to the control sample. It could be hypothesized that the changes in the isotopic abundance and mass peak intensities due to the modification in nuclei possibly through the interference of neutrino particles using the Trivedi Effect®-Consciousness Energy Healing Treatment. The Biofield Energy Treated/Blessed L-tryptophan with increased stable isotopic abundance ratio might have changed the physicochemical properties with higher force constant in the molecule. The new form of treated L-tryptophan would be a better and more stable in the supplements, nutraceutical, and pharmaceutical formulations, which would be advantageous for the prevention and treatment of pellagra, depression, kynurenine. It could also maintain the normal label of tryptophan and avoid increase of its metabolite, lower the neurotoxin and a metabotoxin behavior, glutaric aciduria type I (glutaric acidemia type I) disorder, eosinophilia-myalgia syndrome (EMS), incurable and sometimes fatal flu-like neurological condition, etc. As tryptophan is the precursor for the plant hormones like indole alkaloids and auxins, hence, this treated L-tryptophan would be advantageous for the improvement of yield, productivity, and quality of crops and other plants.
Keywords: L-tryptophan; The Trivedi Effect®; Consciousness Energy Healing Treatment; LC-MS.